1992
DOI: 10.1051/limn/1992023
|View full text |Cite
|
Sign up to set email alerts
|

Etude expérimentale de la dénitrification in situ en eaux courantes : application à la rivière Charente

Abstract: The nitrous oxide determination, after acetylene inhibition of its reduction, was made by GPC. We observed no N20 production in the water. The dénitrification rate, expressed as mg of nitrates. M~ 2 . d~ can be considered as a constant and is independent of the temperature variation, nitrate and dissolved oxygen concentrations of the sediment-water system.On a annual cycle, whithout the marked influence of environmental factors, the mean rate of dénitrification in the river Charente is about 682 mg.m -2 . d~ '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Increases in the input of nitrogen (N) from fertilisers and other sources in recent decades have been reflected in rises in the concentration of combined N in many rivers and other aquatic systems (Royal Commission of Environmental Protection, 1983;Torre et al, 1992). However, mass balance calculations for total N in some Ontario rivers (Hill, 1979(Hill, , 1981(Hill, , 1983) have shown that there was a net loss of N. Among the important processes involved in this loss is denitrification, which is the dissimilatory reduction of nitrate, via nitrite, to the gaseous products, N 2 O and/or N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the input of nitrogen (N) from fertilisers and other sources in recent decades have been reflected in rises in the concentration of combined N in many rivers and other aquatic systems (Royal Commission of Environmental Protection, 1983;Torre et al, 1992). However, mass balance calculations for total N in some Ontario rivers (Hill, 1979(Hill, , 1981(Hill, , 1983) have shown that there was a net loss of N. Among the important processes involved in this loss is denitrification, which is the dissimilatory reduction of nitrate, via nitrite, to the gaseous products, N 2 O and/or N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although rivers are usually the first aquatic system to receive the excess of nitrate, fewer studies have been undertaken on them than on soils or estuaries. Only one (2,27) or a few sites down the river (4) have been sampled, and it is therefore difficult to generalize from the results. According to the river continuum concept of Vannote et al (28), the physical and chemical variables of water and sediments should present a gradient from the headwaters to the estuary, which should elicit a series of responses within the denitrifying bacterial population.…”
mentioning
confidence: 99%
“…For that purpose, several authors have proposed to measure nitrate uptake using benthic chambers in the field (e.g. Chestéri-koff et al 1992, Torre et al 1992, Duff et al 1996. We decided not to choose this method because it prevents atmospheric reaeration due to the complete isolation of the volume of water from the atmosphere.…”
Section: Discussionmentioning
confidence: 99%